Comparison and Evaluation of Fermentation Results of Probiotic Products by Acenobacter xylinum: Komparasi dan Evaluasi Hasil Fermentasi Produk Probiotik dengan Kultur Acenobacter xylinum - Kinanti Lestari; Floreta Fiska Yuliarni; Lailatus Sa’diyah; Silvi Ayu Wulansari; Selvyronica Eka Agustine; Fatma Ariska Trisnawati; Silfiana Nisa Permatasari (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
products with Acetobacter xylinum starter included Nata and Kombucha. The large number of studies on probiotic product innovation should be followed by a survey on public acceptance of the products. This research aim to compare of the yield of probiotic products after fermentation process which was evaluated from a physical perspective, pH and public acceptance. This research is an experimental study to compared the fermented results of two types of probiotic products, nata and kombucha which are differentiated based on their raw ingredients. The nata products sample which had the largest thickness and weight of cellulose biofilm was NDC, while the kombucha products sample which had the largest thickness and weight of cellulose biofilm was KGF. pH of all samples, both nata and kombucha, decreased during the fermentation process. The samples of nata products that were most accepted by the panelists were NDC and NDM in terms of color, smell and taste. The samples of kombucha products that were most accepted by the panelists were KAF and KMF in terms of color, smell and taste.